Géneros textuales/discursivos y tecnologías digitales - Brunel Matias, Richard (org.); Lousada, Gouvêa Eliane (org.); Lopes Cristovão, Vera Lúcia (org.) (FL Copias, 2020)
Fil: Brunel Matias, Richard. Universidad Nacional de Córdoba. Facultad de Lenguas; Argentina.